Various PSO methods investigation in renewable and nonrenewable sources - Madhumathi Periasamy; Thenmalar Kaliannan; Shobana Selvaraj; Veerasundaram Manickam; Sheela Androse Joseph; Johny Renoald Albert (Institute of Advanced Engineering and Science, 2022)
Optimization structures are mostly considered for resolving multi-objective difficulties similar to cost, emission, and financial load dispatch in various energy sources. Non-renewable energy sources (NRES) emit harmful gases like CO2, and methane. which results in air pollutants, so various techniques are used in survey papers. By considering optimization techniques, the multi-objective problems are reduced in renewable energy sources (RES) and NRES. Implementing these techniques in RES and NRES will define the proper objective function. Hybrid algorithms are used for solving multi-objective problems like cost, pollutant emission, price penalty factor, valve point, ramp rates, and constraints like generator, power flow, power balance, and heat balance. A fuzzy system is used in numerous surveys for controlling purpose, superiority, and efficiency over other controllers. Subsequently summarized three types of sources like RES, RES-NRES, and NRES for easy identification of techniques and problems. This study reviews various techniques and mathematical modeling of algorithms for future research.